The men in our living room : masculinities and the struggle for a 'new' South African hegemony in 'Egoli: place of gold' 1994 - Jonker, Francois (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.